POSITIONING OF FRACTURE FEMUR PATIENTS FOR SPINAL ANAESTHESIA: FEMORAL NERVE BLOCK OR INTRAVENOUS FENTANYL? - Kumar, Amarjeet; Sinha, Chandni; Kumar, Ajeet; Kumari, Poonam; Bhadani, Umesh Kumar; Bhar, Ditipriya (Bali Journal of Anesthesiology, 2018)
Background: Fracture of the femur is a common, but extremely painful bone injury. Anaesthesiologists face the common problem of improper positioning of the patient while giving sitting spinal due to their extreme pain.Methods: After Institutional Ethical Committee (IEC) clearance, 60 of American Society of AnaesthesiologistsÂ (ASA) I/II patients age 18 to 80 years with fracture femur were recruited. Patients in Femoral Nerve Block (FNB) group received ultrasound-guided FNB was given with 15 mL of 1% lignocaine after visualizing the femoral nerve. Patients in the fentanyl group received injection fentanyl 1Î¼g/kg IV. The target was to reduce the Visual Analog Scale (VAS) score less than 4. If despite the intervention, VAS was more than 4, a repeat fentanyl dose (0.5Î¼g/kg) was given.Results: Mean VAS during positioning was 1.57 in FNB versus 2.93 in the fentanyl group (p<0.001). An additional dose of fentanyl required was less in FNB group and was more in fentanyl group (p<0.001). Performer rated quality of patient position was more in FNB group (meanÂ±SD) 2.73 + 0.450 while1.47 + .507 in fentanyl group. This difference was statistically more significant (p<0.001). Patients satisfaction was more in the FNB group than fentanyl group (p<0.001) which was highly significant.Conclusion: Ultrasound-guided FNB provides better analgesia, patient satisfaction, less time for anesthesia and satisfactory positioning than IV fentanyl for a central neuraxial block in patients undergoing surgeries for femur fractures.